Ultrasonic transducer for the reception of acoustic emission signals of the temporomandibular joint - SALAMON, R.; LIS, W.; ZIENKIEWICZ, J. (Archives of Acoustics, 1999)
Auscultation and analysis of acoustic signals emitted by the human body are widely used in medical diagnosing. Acoustic signals are also emitted by joints, including the temporomandibular joint, which is the subject of this paper. A system was developed to receive, record, process and display the signals emitted by this particular joint. The article presents an essential fragment of the system, namely a special ultrasonic transducer designed to receive acoustic signals emitted by the temporomandibular joint. At first, the particular requirements were established in the area of the parameters and functions of the transducer. Following that, a technological solution was proposed. Next, a model of the transducer was analysed using the difference equation method with continuous time. The solution of these equations is the pulse response of the transducer and in the frequency domain, it is the shift function. These functions were used for an in-depth analysis of the effects of the transducer’s construction on its parameters and values. Based on these findings, a methodology of the design of the transducer was developed. The transducer was designed and built according to the methodology. It was subsequently studied in detail. The results of the study have confirmed that the method of the analysis and the design were correct. Finally, the article presents some examples of real signals of acoustic emission of the temporomandibular joint as they were received by the ultrasonic transducer built in the course of the work.